Vale dos vinhedos: um estudo de caso sobre denominações de origem e seus regulamentos de uso - Ortenzi, David Medeiros (Universidade do Vale do Rio dos Sinos, 2018)
The research Vale dos Vinhedos: a case study on Appellations of Origin and its Regulations of Use offers an approach on the impacts of the absence of culture of origin in Brazil, proposing that the late adoption of Appellations of Origin in the country brought with it challenges to the adhesion to the Regulation of Use of the Appellations of Origin, when viewed as a standard form contract. Thus, the research seeks to offer a hypothesis to explain the way in which the winemakers of the Appellation of Origin Vale dos Vinhedos are led or not to adhere to its Regulation of Use, considering its instrumentation as a standard form contract. The methodology used was the case study method, from the perspective of Yin, and the chosen case was the Vale dos Vinhedos, in Rio Grande do Sul, the only wine Appellation of Origin in Brazil to date. Numerical data on the production and labeling of wines with the Appellation were collected from the winemakers' association, with also the floating reading of the Regulation of Use and the interview with six wineries - three adherents and three non-adherents. The procedure method chosen was the content analysis, according to Laurence Bardin. The theoretical framework sought to present the Regulations of Use as standard form contracts, exploring the concepts of geographical indication, Appellation of Origin, terroir, legal protection, management and control structures, economic issues - in particular, transaction cost theory and theory of the principal-agent problem, and notions of parties' behavior in standard form contracts. Throughout the research, it was discovered that the Regulation of Use is not a cause of the existing incentives, but a consequence, and that most incentives are for the non-adherence, reinforced by the negative market evolution of the Appellation of Origin Vale dos Vinhedos, while the adherent winemakers are so because they were involved since the conception of the protection and drafting of the Regulation of Use. A theoretical framework for evaluating future Appellations of Origin is proposed, and also a practical contribution for the proposition/creation of future Appellations of Origin and self-evaluation of the existing ones.
Keywords: Propriedade intelectual; Denominações de origem; Regulamento de Uso; Custos de transação; Problema do principal-agente; Intellectual property; Appellations of origin; Regulation of Use; Transaction costs; Principal-agent problem; ACCNPQ::Ciências Sociais Aplicadas::Direito